2015
DOI: 10.1136/bmjopen-2015-009476
|View full text |Cite
|
Sign up to set email alerts
|

Burden of poor oral health in older age: findings from a population-based study of older British men

Abstract: ObjectivesEvidence of the extent of poor oral health in the older UK adult population is limited. We describe the prevalence of oral health conditions, using objective clinical and subjective measures, in a population-based study of older men.DesignCross-sectional study.Setting and participantsA representative sample of men aged 71–92 years in 2010–2012 from the British Regional Heart Study, initially recruited in 1978–1980 from general practices across Britain. Physical examination among 1660 men included the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(100 citation statements)
references
References 22 publications
6
87
0
3
Order By: Relevance
“…Higher CPITN scores were associated with the adult than the adolescent sample, and increasing age was a significant predictor of CPITN score severity when all other background and behavioral factors were taken into account. This general increase in CPITN scores or in other indicators of periodontitis with increasing age has been similarly reported in earlier investigations[16171819] and may be due to the cumulative effects of calculus and the progressive nature of periodontal disease and the cumulative effects of periodontal breakdown over time. [20] Our results also support previous assessments of intellectual disabled populations reporting low prevalence of healthy periodontium and the predominance of bleeding and calculus.…”
Section: Discussionsupporting
confidence: 84%
“…Higher CPITN scores were associated with the adult than the adolescent sample, and increasing age was a significant predictor of CPITN score severity when all other background and behavioral factors were taken into account. This general increase in CPITN scores or in other indicators of periodontitis with increasing age has been similarly reported in earlier investigations[16171819] and may be due to the cumulative effects of calculus and the progressive nature of periodontal disease and the cumulative effects of periodontal breakdown over time. [20] Our results also support previous assessments of intellectual disabled populations reporting low prevalence of healthy periodontium and the predominance of bleeding and calculus.…”
Section: Discussionsupporting
confidence: 84%
“…Poor oral health, which includes periodontitis, caries, and edentulism, is one of the most common medical conditions worldwide. Severe periodontitis has been reported to be the sixth most prevalent condition worldwide and is more prevalent in elderly people than in the general population . Periodontitis is an inflammatory disease in which multiple microorganisms infect the tissues that support the teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Population‐based studies have shown that prevalence of oral impacts on the quality of life of older people ranged between 14% and 57.8% worldwide . Other less representative cross‐sectional studies have found prevalence of OIDP ranging between 57.9% and 92.7% .…”
Section: Discussionmentioning
confidence: 99%
“…The impact of oral health conditions on the population's well‐being and quality of life has been remarkably investigated worldwide . Nevertheless, not all investigations are population‐based studies.…”
Section: Introductionmentioning
confidence: 99%